Structural and photoluminescence analysis on the implantation of carbon and proton for the creation of damage-assisted emission in silicon - Nurul Ellena Abdul Razak,; Madhuku, Morgan; Ahmad, Ishaq; Burhanuddin Yeop Majlis,; Chang, Fu Dee; Dilla Duryha Berhanuddin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
We study the induced defects in the depth profiling of the silicon structure after being implanted with carbon and followed by high energy proton irradiation. It has been reported before that the formation of the optically active pointdefect, specifically the G-centre is due to the implantation and irradiation of carbon and proton, respectively. It is crucial to quantify the diffusional broadening of the implanted ion profile especially for proton irradiation process so that the radiation damage evolution can be maximized at the point-defect formation region. Profiling analysis was carried out using computational Stopping and Range of Ions in Matter (SRIM) and Surrey University Sputter Profile Resolution from Energy Deposition (SUSPRE) simulation. The energies of carbon ions adopted for this investigation are 10, 20, 30, and 50 keV, while proton irradiation energy was kept at 2 MeV. Photoluminescence measurements on silicon implanted with carbon at different energies were carried out to study the interrelation between the numbers of vacancies produced during the damage event and the peak emission intensities.